Development and Usability of a Smartphone Application for Tracking Antiretroviral Medication Refill Data for Human Immunodeficiency Virus - Coppock, Dagan; Zambo, Dikai; Moyo, Dumisani; Tanthuma, Gobe; Chapman, Jennifer; Re, Vincent Lo, III; Graziani, Amelia; Lowenthal, Elizabeth; Hanrahan, Nancy; Littman-Quinn, Ryan; Kovarik, Carrie; Albarracin, Dolores; Holmes, John H.; Gross, Robert (Methods of Information in Medicine, 2017)
Background: Adherence to antiretroviral medication leads to HIV suppression and decreased morbidity and mortality. In resource- limited settings, the dependence on paper medical charts and unstable electronic health records creates a challenge to monitoring medication adherence. A pharmacy-based strategy that utilizes existing cellular phone infrastructure may lead to a more stable system to monitor adherence.Objectives: To develop and evaluate the usability of a smartphone-based software application (app) for tracking antiretroviral medication refill data in a resource-limited setting.Methods: A pharmacy-based smartphone app for tracking HIV medication adherence was developed through a multi-step rapid prototyping process. The usability of the app was assessed during the daily activities of pharmacy dispensers at HIV clinics in and around Gaborone, Botswana using a validated computer usability survey.Results: The study demonstrated the effective development of and favorable end-user responses to a pharmacy-based HIV medication adherence app. End users had suggestions for minor changes to improve the app’s functionality.Conclusions: In resource-limited settings where electronic health record support is limited, such a system was feasible and appealing. In the future, this system may allow for improved HIV medication adherence tracking and be applied to medications beyond antiretrovirals.
Keywords: Medical informatics; smartphone; mobile applications; medication adherence; HIV